The social construction of beauty in the digital era: Gen z's interpretation of beauty standards in Jakarta - Yens, Diva; Syuhada, Nisa Haniatus; Rajaby, Wardah; Fauzi, Rizky Ahmad; Putra, Elok; Maulana, Moh. Faiz; Lestari, Putri (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
This study aims to understand how Generation Z in Jakarta perceives beauty as constructed by social media, with a focus on beauty standards often shaped by homogeneous representations. These standards influence individuals' perceptions of beauty, which in turn shape their identity and self-image. This research employs Berger’s social construction theory to analyse how social media functions as a primary agent in shaping perceptions of beauty. A qualitative-descriptive approach is employed to explore the experiences and perceptions of Generation Z regarding these beauty standards. Data were collected through semi-structured interviews, participatory observation, and content analysis of social media. Informants were selected using purposive sampling, with a total of six people chosen as informants and actively consuming beauty content on social media. They come from diverse backgrounds to provide a more comprehensive perspective. The findings indicate that social media, particularly Instagram, plays a significant role in internalizing homogeneous beauty standards, such as fair skin and slim bodies. However, a growing resistance movement among Generation Z advocates for diversity and inclusivity in defining beauty. This study highlights the importance of critical education regarding the impact of social media on beauty perceptions and the need to introduce more diverse and unrestricted representations of beauty.